Interaksi Parasosial Penggemar Nike Ardilla yang tergabung Dalam “Nike Ardilla Fans Club” - Wahyudi Yusron; Erman Anom (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore parasocial interactions between fans and public figures who have died, with a focus on the extraordinary phenomenon related to the persistence of the influence of these figures even after they have died. The research method used is a qualitative approach with case studies. The research results showed that the majority of informants showed characteristics of parasocial interactions, such as Imaginary Friendship, Search for Friendship, Empathy towards Idols, and Reality of Relationships. In the context of the parasocial level of interaction, most of the informants experienced Entertainment Social Value and Intense Personal Feelings, while none showed signs of Borderline Pathological Tendencies. This indicates that the parasocial interactions that occur are still within normal limits. The conclusion is that parasocial interactions between fans and public figures who are no longer alive can take place with high intensity, even though the figure has died. Despite this, the majority of fans remained within normal limits in their interactions, without showing any worrying pathological signs. Keywords: Parasocial Interaction, Nike Ardilla Fans Club, Public Figures